Effect of anode–cathode distance and anodizing time on hardcoat anodizing of AA7075 - Tito Endramawan; Emin Haris; Yusup Nur Rohmat; Candra Irawan (Jurnal Polimesin, 2026)
Fishing activities in Indramayu ( a seaside city in West Java) typically use boats powered by propellers. These propellers often strike floating objects, resulting in damage such as cracked or broken blades. A survey revealed that the fractures are mainly caused by the poor quality of propellers produced using the gravity casting technique, which results in rough surfaces with pores and cracks that initiate during finishing. Therefore, surface repair is necessary, and one potential method is hardcoat anodizing. This study aims to investigate the effect of coating time and anode–cathode distance on the hardness of the oxide layer formed during the hardcoat anodizing process of AA7075 aluminum alloy. The anode–cathode distances were 5 cm, 10 cm, and 15 cm, with coating times of 40, 50, and 60 minutes. The process was conducted at 2 to 3°C, with a current of 5.12 A and a voltage of 31.5 V. The results of micro-Vickers hardness testing, conducted with a loading parameter of 200 gf and an indentation time of 15 seconds, indicated a hardness increase of 256% compared to the base material. The highest hardness value was achieved at a distance of 5 cm and a coating time of 60 minutes, measuring 322.9 VHN, with a resulting layer thickness of 67.16 µm.